-6+3=-2x+1

Simple and best practice solution for -6+3=-2x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+3=-2x+1 equation:


Simplifying
-6 + 3 = -2x + 1

Combine like terms: -6 + 3 = -3
-3 = -2x + 1

Reorder the terms:
-3 = 1 + -2x

Solving
-3 = 1 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-3 + 2x = 1 + -2x + 2x

Combine like terms: -2x + 2x = 0
-3 + 2x = 1 + 0
-3 + 2x = 1

Add '3' to each side of the equation.
-3 + 3 + 2x = 1 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = 1 + 3
2x = 1 + 3

Combine like terms: 1 + 3 = 4
2x = 4

Divide each side by '2'.
x = 2

Simplifying
x = 2

See similar equations:

| 2z^4-3z^2+1=0 | | 8(c-2)+3-2=2c+15 | | 2n+8=44 | | 9-x+4=2 | | 5x-7x-7=2x+5-7 | | D^2=13x | | (3x+14)=(5x+20) | | -14+5k=k-3k | | 3m+6+6=m-18 | | -99=-3(3x+7)-6 | | 2(s-6)=4 | | 9y-y=-14+y | | (2x)+16=48 | | C+c+3=53 | | (8x+5)+(4x-5)=180 | | 2(-5)+y=6 | | C-7=5.3 | | 15-2/3x=9 | | y-9=6/7(x-4) | | ln(a+10)+5=7 | | (1-3)x+5=6x+-8 | | 2x+5+3x+10=100 | | 3.5h=2h-12 | | 10(4x+2)=3(8-x)+6 | | 8x+5+4x-5=180 | | y-9=6/7)x-4) | | 0.83t^2-10t+31=0 | | 2n+11=10 | | -14=7(y-5) | | -2=7-v | | 7-2a=54 | | 10+e-5+e=5(e-1) |

Equations solver categories